Fever in travelers returning from tropical and subtropical areas: a hospital-based study of factors affecting investigations and diagnoses in children and adults - Klara Sondén; Donya Satarvandi; Helena Hildenwall; Sara Falck-Jones; Victor Yman; Niclas Johansson; Katja Wyss; Elin Folkesson; Hilmir Asgeirsson; Irene Nordling; Anna Löwhagen Welander; Anna Färnert (Travel Medicine and Infectious Disease)
Background: As global travel surges in the post-pandemic era, healthcare systems must prepare for proper management of diseases encountered by returning travelers. Method: A retrospective study of the management of returning travelers from tropical or subtropical regions, with fever at the adult and paediatric emergency departments of Karolinska University Hospital, Stockholm Sweden. Demographics, travel history, clinical and microbiology data were extracted from health records. Multivariate regression analyses identified factors affecting investigations and diagnoses. Results: A total of 2441 patients (2197 adults, 244 children) were included. An etiological diagnosis was confirmed in 63.3 % (n = 1546) of patients; with malaria (5.6 %, n = 138), dengue (4.0 %, n = 98) and typhoid fever (0.9 %, n = 22) being the most common tropical infections. Patients with fever >38 °C (aOR 1.48, 95 % CI 1.20–1.84) or hospitalization (aOR 4.68, 95 % CI 3.23–6.80) had higher odds of etiological diagnosis. Children were less likely than adults to have a cause of fever diagnosed (OR 0.64, 95 % CI 0.49–0.84). Malaria testing was lower in children than adults who had visited Sub-Sahara Africa (80.6 % vs 90.4 %). Overall, a lower proportion of children underwent blood cultures, compared to adults (29.5 % vs 68.7 %). VFR travelers and migrants had lower probability of other microbiological investigations when malaria testing was negative (aOR 0.69, 95 % CI 0.54–0.90; aOR 0.67, 95 % CI 0.50–0.90). Conclusion: The management of febrile patients following tropical travel varied significantly across different patient groups. Children, migrants and VFR travelers often receive less thoroughly investigations. This highlights the need for equitable management and investigation, especially for these vulnerable populations.